2011
DOI: 10.5012/bkcs.2011.32.2.673
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Approaches to the Molecular Structure of 3-(2-Mercaptopyridine)phthalonitrile

Abstract: The compound 3-(2-Mercaptopyridine)phthalonitrile has been synthesized and characterized by IR, UV-vis, and X-ray single-crystal determination. The molecular geometry from X-ray determination of the title compound in the ground state has been compared using the Hartree-Fock (HF) and density functional theory (DFT) with the 6-31G(d) basis set. The calculated results show that the DFT and HF can well reproduce the structure of the title compound. The energetic behavior of the title compound in solvent media was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…If the cyano groups are considered in the molecule, the C-C-N bond angles can be seen that near-linear. As expected, the N-C-C angles [N1-C7-C4=177.6(3)°and N2-C8-C5=178.6(3)°] are almost linear and in a good agreement with previously reported values by [36][37][38][39]. In our calculation these angles were calculated as 178.4°and 178.05 for using B3LYP method, respectively.…”
Section: Description Of the Crystal Structuresupporting
confidence: 80%
“…If the cyano groups are considered in the molecule, the C-C-N bond angles can be seen that near-linear. As expected, the N-C-C angles [N1-C7-C4=177.6(3)°and N2-C8-C5=178.6(3)°] are almost linear and in a good agreement with previously reported values by [36][37][38][39]. In our calculation these angles were calculated as 178.4°and 178.05 for using B3LYP method, respectively.…”
Section: Description Of the Crystal Structuresupporting
confidence: 80%
“…The frequency values computed at the calculation level contain known systematic errors. Therefore, 0.9613 was selected as the scaling factor [49]. Selected theoretical and experimental vibrational data are shown in Table 2.…”
Section: Assignments Of the Vibrational Modes Of The Compound (3)mentioning
confidence: 99%
“…The harmonic vibrational frequencies were calculated at the same level of the theory for the optimized geometry of the compound (3). Absence of the imaginary frequency indicated that the structure was in global minimum and obtained vibrational frequencies were scaled by 0.9613 [49]. Vibrational frequency assignments were done by using Gauss-view molecular visualization software [50].…”
Section: Computational Detailsmentioning
confidence: 99%
“…In consequence, the bond is not intense, and it falls at lower frequencies. Identification is therefore difficult and uncertain [40]. In this study, the theoretically scaled vibrations by HF/6-311++G(d,p) and DFT/B3LYP/6-311++G(d,p) methods at 708, 695, 681, and 568 cm -1 and 696, 686, 676, and 553 cm -1 , respectively, are assigned to ν(SC) stretching vibrations.…”
Section: C=n C-n and C-s Vibrationsmentioning
confidence: 99%